2012
DOI: 10.1100/2012/653098
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Associated Factors for Anxiety and Depression in Pregnant Women: A Hospital-Based Cross-Sectional Study

Abstract: Antepartum anxiety and/or depression is a major public health problem globally. The aim of this study was to estimate the frequency of antepartum anxiety and/or depression among pregnant women. This was a cross-sectional study conducted in a tertiary care hospital among pregnant women. A total of 165 pregnant women were interviewed by a clinical psychologist using HADS for assessing anxiety and/or depression and also collected information regarding sociodemographic, obstetric, family relationships, and home en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
112
2
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(147 citation statements)
references
References 44 publications
19
112
2
10
Order By: Relevance
“…Similar findings were reported by Niolufer (Ali et al, 2012) (20.4% and 16.8%) who conducted the study using HADS in a hospital setting. The rates of anxiety and depression disorder diagnosed through MINI interview were 9.1% and 8.6%, respectively.…”
Section: Discussion Prevalence Rates Of Antenatal Anxiety and Depresssupporting
confidence: 79%
“…Similar findings were reported by Niolufer (Ali et al, 2012) (20.4% and 16.8%) who conducted the study using HADS in a hospital setting. The rates of anxiety and depression disorder diagnosed through MINI interview were 9.1% and 8.6%, respectively.…”
Section: Discussion Prevalence Rates Of Antenatal Anxiety and Depresssupporting
confidence: 79%
“…Thus, the characterization of the participants of this study resembled that of other studies regarding age and marital status (4) , however it differs from other studies regarding income and educational level (6) . Considering the incidence of anxiety during pregnancy, there are no homogeneous data.…”
Section: Discussionmentioning
confidence: 57%
“…In the present study, 26.8% (56) of the pregnant women presented anxiety during pregnancy. In a study conducted in Pakistan (4) , which also used the Hospital Anxiety Subscale as an instrument to assess this disorder, the prevalence of anxiety among pregnant women was 20.4%. Different data were found by a study carried out in South Africa, which used another instrument and found a rate of 11.8% of anxious pregnant women (17) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En un porcentaje importante, son pacientes que tienen antecedentes de haber sufrido episodios depresivos anteriormente. Estos datos son concordantes con la literatura internacional y nacional que indica que la depresión afecta más frecuentemente a mujeres en edad fértil 29 .…”
Section: Discussionunclassified